Changes in growth, survival and digestive enzyme activities of Asian redtail catfish, Mystus nemurus, larvae fed on different diets - Kamarudin, Mohd Salleh; Otoi, Samsiah; Saad, Che Roos (Academic Journals, 2011)
A study was conducted to determine the effects of different dietary treatments on the growth, survival and digestive enzyme activities of Mystus nemurus larvae. Newly hatched larvae were reared for 14 days in twelve 15 L glass aquaria (for growth and survival) and eight 300 L fiberglass tanks (for enzyme samples) at a stocking density of 15 larvae L-1. Beginning at 2 days, the larvae were randomly assigned to Artemia nauplii, a microbound diet and a 50:50 combination of live food-microbound diet, while another group was unfed. All treatments were triplicated (growth and survival) or duplicated (enzyme development). The results showed that, M. nemurus larvae which fed on Artemia nauplii gave the highest survival rate (83.7%), followed by those fed on a combination diet (56.0%) and a microbound diet (26.5%). All unfed larvae did not survive beyond Day 9. Artemia had also given the best growth (20.4 ± 1.4 mm TL and 37.2 ± 6.0 mg wet weight) for the catfish larvae. This was followed by the combination diet (18.3 ± 0.6 mm TL and 32.6 ± 3.4 mg wet weight) and the microbound diet (11.0 ± 0.1 mm TL and 11.9 ± 0.9 mg wet weight), respectively. Pepsin began to significantly appear in M. nemurus larvae at 4 days old for all treatments, while chymotrypsin, trypsin and amylase were present even in the newly hatched larvae. In general, highest enzyme activities were observed among larvae which fed on a combination diet, followed by those fed on live and artificial diets, respectively. This suggested the important role of exogenous enzymes from live food in the larval digestion particularly at the early feeding stages.